CMOS imaging for automotive applications. - Hosticka, B.J (IEEE Transactions on electron devices)
This contribution is devoted to CMOS imaging for automotive applications. It is shown that unlike CCD-based imaging, imaging based on CMOS-sensing meets adequately requirements posed by automotive vision applications. In addition, besides classical vision, CMOS imaging enables new applications like, e.g., occupancy sensing, rangefinding, and 3-D vision.